Reducing PAPR in PRS-OFDM system using Fraction Time-Selective (FTS) envelope modification - Syed Yusof, Sharifah Kamilah (2007)
Orthogonal Frequency Division Multiplexing (OFDM) is the most promising technique for next generation broadband wireless communication system. The major setbacks of OFDM signal are intercarrier interference (ICI) and high peakto- average power ratio (PAPR). The purpose of this thesis is to develop mechanisms to reduce ICI and PAPR in OFDM systems. Partial response signaling OFDM (PRS-OFDM) with integer coefficient system has been developed to minimise the ICI. The carrier-to-interference power ratio (CIR) is enhanced by 2.6 dB to 5 dB compared to the normal OFDM. The PAPR has been reduced using Fraction Time-Selective (FTS) Envelope Modification technique. The FTS Envelope Modification PRSOFDM managed to reduce the PAPR by 0.8 dB to 2.8 dB. Efficient bandwidth usage is achieved by manipulating the PRSOFDM signal characteristics, where minimal side information (SI) is required due to restricted envelope modification factors